1994
DOI: 10.1042/bj3030957
|View full text |Cite
|
Sign up to set email alerts
|

β1-4N-acetylgalactosaminyltransferase can synthesize both asialoglycosphingolipid GM2 and glycosphingolipid GM2in vitro and in vivo: isolation and characterization of a β1-4N-acetylgalactosaminyltransferase cDNA clone from rat ascites hepatoma cell line AH7974F

Abstract: We have cloned a cDNA encoding beta 1-4N-acetylgalactosaminyltransferase (EC 2.4.1.92) (GalNAc-T) from rat ascites hepatoma of the free-cell type AH7974F. The cell line only expressed asialo-series glycosphingolipids (GSLs) including asialo-GM2 [Taki, T., Hirabayashi, Y., Ishiwata, Y., Matsumoto, M., and Kojima, K. (1979) Biochim. Biophys. Acta 572, 113-120]. The cDNA, pGNA56, was isolated by screening AH7974F cDNA library in lambda gt10 with a probe. The probe was obtained from AH7974F cDNA by PCR using prime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Previous studies demonstrated that PA-sugar chains are good substrates for glycosyltransferases [22,30,31]. In Figure 4, under our HPLC conditions, PA-001 was commonly eluted around at 7 min post injection.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Previous studies demonstrated that PA-sugar chains are good substrates for glycosyltransferases [22,30,31]. In Figure 4, under our HPLC conditions, PA-001 was commonly eluted around at 7 min post injection.…”
Section: Resultsmentioning
confidence: 80%
“…(I) HPLC-based assay: The assay for PAoligosaccharide as an acceptor was carried out as described previously [30,31]. Sialylated products were resolved on an HPLC system equipped with an ion-exchange column, PALPAK Type N (6.4 mm × 25 cm) (Takara Bio, Inc.).…”
Section: Sialyltransferase Assaymentioning
confidence: 99%
“…Thus, cathepsin D or another unknown cathepsin D-like protease appeared to mediate the release of GalNAcT/myc from transfected CHO cells. Interestingly, the apparent cathepsin D cleavage site that we have identified in human GalNAcT, LL2YASTR (Table II), is also present in the rat homolog (18) and only slightly modified (LL2YSSTR) in the murine homolog. 4 The soluble form of GalNAcT released into the culture medium appeared as an intermolecular disulfide-bonded species of a size consistent with that of a homodimer (Fig.…”
Section: Figmentioning
confidence: 99%
“…The GalNac T gene is highly expressed in tumor cell lines such as neuroblastoma and melanoma cell lines [83,84], and in mouse brain at the late stage of development [18,59]. The 5′-flanking fragment of the human GalNac T gene was the first cloned promoter for a ganglioside synthase gene [85].…”
Section: Promoter Of the Galnac T (Ga2/gm2/gd2/gt2-synthase) Genementioning
confidence: 99%
“…The cDNA for GalNAc T has been cloned from human [58], rat [59], and mouse [60,61]. The gene consists of 11 exons.…”
Section: Galnac T (Ec 24192)mentioning
confidence: 99%